Analisis Faktor Yang Mempengaruhi Peningkatan Jumlah Penduduk Di Desa Topogaro Kecamatan Bungku Barat Kabupaten Morowali - Azis, Rafiudin; Adam, Adam; Hasriani, Hasriani (Journal of Islamic Community and Development, 2026)
The population of Topogaro Village based on the population projection for 2022 is only 1,832 people, compared to the population projection for 2023 of 3,886 people, the number has doubled from the previous year. The purpose of this study is: to determine the factors that influence the increase in population in Topogaro Village, and to determine the most dominant factor in the increase in population in Topogaro Village. This study uses a descriptive quantitative method with secondary data obtained through documentation from the Topogaro Village Office and BPS Morowali. The results of the study indicate that: fertility, mortality, and migration are factors that influence the increase in population in Topogaro Village. And Migration is the most dominant factor influencing the increase in population in Topogaro Village in 2023. The suggestions from this study are: the village government needs to improve the accuracy of population records, especially regarding migration, public health programs need to be strengthened to maintain the balance of births and deaths, the village government needs to prepare data-based policies to deal with the surge in migration, further research needs to use a longer time span, research variables can be expanded such as education, economy, or local policies.